Physical diagnosis : - Willms, Janice L. (Williams & Wilkins, 1994)
This textbook on clinical assessment is designed to teach beginning students fundamental skills for the physical examination, as well as to provide advanced learners with a comprehensive reference. Introductory chapters present general history, taking an overview of the examination and a description of vital statistics. Chapters are divided into two sections: screening and extended examination. Contents are organized by anatomic region and include information on cost containment in medical diagnostics. Summary tables of selected narrative include interviewing techniques, examination sequence, normal variant and indications for extended examination